2016
DOI: 10.1139/cjps-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

First report: spotted knapweed (Centaurea stoebe) resistance to auxinic herbicides

Abstract: Spotted knapweed is a prohibited noxious weed that is primarily controlled with auxinic herbicides. A population collected from a managed rangeland in East Kootenay, BC, was highly resistant to both clopyralid and picloram, with R/S ratios of >25 600 and 28, respectively. This is the first report of resistance in spotted knapweed. Résumé: La centaurée maculée est une adventice nocive interdite que l'on détruit principalement avec des désherbants à auxine. Un peuplement résistant au clopyralid et au picloram (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…], wild mustard, and yellow starthistle (Beckie and Tardif 2012; Miller et al 2001), resistance that is specific to herbicides within a chemical family may also occur. For example, Mangin and Hall (2016) reported that spotted knapweed was highly resistant to clopyralid and picloram but not cross-resistant to 2,4-D. Resistance in this buckhorn plantain R biotype was limited to within a chemical family (phenoxycarboxylic acid) and not across all WSSA Group 4 synthetic auxin herbicides, as the pyridinecarboxylic acid herbicides clopyralid and triclopyr and the arylpicolinate herbicide halauxifen-methyl provided control in field or greenhouse experiments. This lack of cross-resistance is possibly attributable to pyridinecarboxylic acid herbicides having higher than average binding activity or a preferred site of action for AFB5, whereas AFB1, AFB2, and AFB3 are thought to preferentially bind to 2,4-D (Dharmasiri et al 2005; Lee et al 2013; Walsh et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…], wild mustard, and yellow starthistle (Beckie and Tardif 2012; Miller et al 2001), resistance that is specific to herbicides within a chemical family may also occur. For example, Mangin and Hall (2016) reported that spotted knapweed was highly resistant to clopyralid and picloram but not cross-resistant to 2,4-D. Resistance in this buckhorn plantain R biotype was limited to within a chemical family (phenoxycarboxylic acid) and not across all WSSA Group 4 synthetic auxin herbicides, as the pyridinecarboxylic acid herbicides clopyralid and triclopyr and the arylpicolinate herbicide halauxifen-methyl provided control in field or greenhouse experiments. This lack of cross-resistance is possibly attributable to pyridinecarboxylic acid herbicides having higher than average binding activity or a preferred site of action for AFB5, whereas AFB1, AFB2, and AFB3 are thought to preferentially bind to 2,4-D (Dharmasiri et al 2005; Lee et al 2013; Walsh et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…At a constant high concentration, auxin herbicides trigger molecular events, known as auxin overdose, that lead to growth anomalies and, ultimately, to cell death . IAA and synthetic analogues, such as 2-methoxy-3,5-dichloro-benzoic acid (dicamba) and 3,5-dichloro-pyridine-2-carboxylic acid (clopyralide), , have been shown to bind to a variety of plant receptors, including the auxin binding protein (ABP1) and the transport inhibitor response (TIR1) protein, which trigger a deregulated growth phase, followed by growth inhibition and cell death . During the growth phase, the transcription of auxin response genes boosts ethylene biosynthesis in the shoots, leading to a downward curvature of leaves (leaf epinasty) .…”
Section: Discussionmentioning
confidence: 99%
“…JID: RAMA [mUS5Gb;May 21, 2020;5:0 ] tance (but see Mangin and Hall 2016 ). However, there are many examples in grasslands systems where management strategies relying on a single tool are ineffective at long-term control, such as a recent review of Canada thistle management ( Davis et al 2018 ).…”
Section: Article In Pressmentioning
confidence: 99%